THE SEARCH FOR NATURAL HYPHOMYCETES TO SUPPRESS THE NUMBER OF HARMFUL LOCUSTS - Charykova, I.V.; Nekrasova, N.I.; Balpanov, D.S.; Ten , O.A. (Eurasian Journal of Applied Biotechnology, 2014)
In various natural and economic zones of Kazakhstan there live about 270 species of locusts. About 15-20 species are of great danger to agricultural lands. The search for natural entomopathogenic hyphomycetes active against pest species of locusts, possessing increased productivity of viable conidia and promising for the development of a biological insecticide preparation has been performed. Fieldwork to find entomopathogenic fungi was carried out in the steppe areas of Akmola region, around Stepnogorsk city and in Kostanai region in 2012: in the foci of mass reproduction, as well as when examining the steppe zones, populated by single individuals of nongregarious locusts. The main place where dead insects were gathered was the soil in the place of concentration of nongregarious locusts. As a result of the directional variation of productivity of the most active culture isolated from natural sources, the strain of the fungus Beauveria bassiana (Va1s.) Vuі11 B-3 which has a high potential: high activity of enzymes and virulence against larvae of the Asian migratory locust (Locusta migratoria L.), good sporulation, viability and productivity has been obtained.